2004
DOI: 10.1002/pssb.200402016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of (CuInSe2)1−x(CoSe)x alloys in the composition range 0 ≤ x ≤ 2/3

Abstract: Polycrystalline samples of (CuInSe 2 ) 1-x (CoSe) x alloys were prepared by the normal melt and anneal technique in the composition range 0 < x ≤ 2/3. The obtained ingots were characterized by scanning electron microscopy, X-ray diffraction and differential thermal analysis techniques. A sample with x = 2/3 (prepared a posteriori) was also studied by the Raman shift technique. The results showed a complex behavior of the phase diagram. The phase (α) with chalcopyrite structure exists in a narrow interval 0 < x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on the literature review, the I-II 2 -III-VI 4 family (I = Cu, Ag; II = Zn, Cd; III = Ga, In; and VI = S, Se) compounds are reported to have a tetragonal structure, close to the parent chalcopyrite structure. [7][8][9][10][11] Delgado et al (2008) determined that CuFe 2 InSe 4 crystallizes in the tetragonal stannite structure, space group I% 42m. 9 Chen et al 12 have calculated the stability of several crystal phases from a cation cross-substitution perspective and found that the stannite structure generally has a higher energy than the kesterite structure after relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature review, the I-II 2 -III-VI 4 family (I = Cu, Ag; II = Zn, Cd; III = Ga, In; and VI = S, Se) compounds are reported to have a tetragonal structure, close to the parent chalcopyrite structure. [7][8][9][10][11] Delgado et al (2008) determined that CuFe 2 InSe 4 crystallizes in the tetragonal stannite structure, space group I% 42m. 9 Chen et al 12 have calculated the stability of several crystal phases from a cation cross-substitution perspective and found that the stannite structure generally has a higher energy than the kesterite structure after relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…The present work, where we have studied the solid solubility of VSe in AgInSe 2 in the composition range of interest, i.e. 0 ≤ x ≤ 0.5, is a part of a systematic study on (I-III-VI 2 )-(TM-VI) alloys [6][7][8][9].…”
mentioning
confidence: 99%
“…466 Several other vibrational spectroscopic studies have been made of cobalt oxide-containing materials. 473 The IR spectrum of the reaction products of co-condensation of Al 2 Cl 6 and CoCl 2 vapours showed the formation of an (AlCl 3 ) 2 CoCl 2 complex. 472 Raman spectroscopy was used to characterise (CuInSe 2 ) 1/3 (CoSe) 2/3 crystals.…”
Section: Cobalt Rhodium and Iridiummentioning
confidence: 97%